Body Temperature Enhanced Adhesive, Antibacterial, and Recyclable Ionic Hydrogel for Epidermal Electrophysiological Monitoring. Issue 15 (19th June 2022) - Liu, Ying; Wang, Chan; Xue, Jiangtao; Huang, Guanhua; Zheng, Shuang; Zhao, Ke; Huang, Jing; Wang, Yiqian; Zhang, Yan; Yin, Tailang; Li, Zhou
Abstract: Hydrogel‐based epidermal electrodes attract widespread attention in health monitoring and human‐machine interfaces for their good biocompatibility, skin‐matched Young's modulus, and stable in situ electrophysiological recording performance. However, it is difficult to make the exact conformal attachment between skin and electrodes because of the hair, wrinkles, as well as complex, curved contours of the skin. This also results in signal distortion and large noise. Here, a body temperature enhanced skin‐adhesive epidermal electrode is proposed based on non‐covalent cross‐linked network ionic hydrogel. The ionic hydrogel is fabricated by the polyvinyl alcohol, branched polyethyleneimine, and calcium chloride (CaCl2 ), which demonstrates impressive performances including ultra‐stretchability of 1291%, great adhesion to skin and other non‐biological materials, stable conductivity of 3.09 S m −1, recyclability, and outstanding antibacterial ability, simultaneously. Specifically, the adhesion of the ionic hydrogel behaves as temperature‐sensitive and could be enhanced by body temperature. Furthermore, the ionic hydrogel is utilized as epidermal electrodes, which display seductive capability to record multifarious electrophysiological signals with high signal‐to‐noise ratio and ultra‐low detection limit, including electrocardiogram, electromyogram, and electroencephalogram. The as‐proposed body temperature enhanced skin‐adhesive ionic hydrogel brings intelligent functions and broadens the way for epidermal electronics, promoting the development of healthcare electronics. Abstract : The multifunctional ionic hydrogel (MiH) is equipped with body‐temperature enhanced adhesion, stretchability, recyclability and antibacterial properties based on dual physical cross‐linked network. When applied as the epidermal electrode, the MiH builds a highly compliant and gapless interface with the skin to monitor high‐fidelity electrophysiological signals which broadens the way for epidermal electronics and promotes the development of healthcare electronics.